PEMANFAATAN EGRANG DALAM PEMBELAJARAN OLAHRAGA UNTUK MENINGKATKAN HASIL BELAJAR DAN KOLABORASI PADA SISWA KELAS IV SEKOLAH DASAR - Purnamaningtyas, Dwi Yusta; Andi Kristanto; Hendratno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the use of traditional stilt games in sports learning as an effort to improve learning outcomes and collaboration skills of elementary school students. Stilts, as a game that requires balance and physical skills, have the potential to enrich sports learning that not only focuses on physical aspects, but also social aspects, such as cooperation and mutual support between students. The research method used is descriptive qualitative with an observation, interview, and documentation approach. The participants of this study were 4th grade students at SDN Bohar Sidoarjo. Through observation and in-depth interviews, it was found that the use of stilts in learning was not only able to improve students' physical agility, but also strengthen collaboration and cooperation skills in groups. Stilt-based sports learning encourages students to help each other and build self-confidence in trying new things, as well as fostering an appreciation for traditional games as part of cultural heritage. The results of this study indicate that learning involving traditional games such as stilts can be an effective method in building students' physical and social abilities in an integrated manner, while supporting the preservation of local culture in elementary school environments.